Deformation Study of Papandayan Volcano using GPS Survey Method and Its Correlation with Seismic Data Observation - Sarsito, Dina A.; Andreas, Heri; Abidin, Hasanuddin Z.; Gamal, Muhammad; Suganda, Ony K.; Hendrasto, Muhammad (ITB Journal Publisher, LPPM ITB, 2006)
Papandayan volcano located in the southern part of Garut regency, around 70 km away from Bandung city, West Java. Many methods carried out to monitoring the activities of volcano, both continuously or periodically, one of the monitoring method is periodically GPS survey. Basically those surveys are carried out to understand the pattern and velocity of displacement which occurred in the volcano body, both horizontally and vertically, and also others deformation elements such as; translation, rotation and dilatation. The Mogi modeling was also used to determine the location and volume of the pressure source which caused deformation of volcano body. By comparing seismic activity and the deformation reveal from GPS measurement, before, during and after eruption, it could be understood there is a correlation between the seismicity and its deformation. These studies is hoping that GPS measurement in Papandayan volcano could be one of supported method to determine the volcano activities, at least in Papandayan volcano.